Intelligence science II : third IFIP TC 12 International Conference, ICIS 2018, Beijing, China, November 2-5, 2018, Proceedings /: third IFIP TC 12 International Conference, ICIS 2018, Beijing, China, November 2-5, 2018, Proceedings. (2018) - Unknown
No abstract available